Design and experiment of a six-row air-blowing centralized precision seed-metering device for Panax notoginseng - Lai, Qinghui; Sun, Kai; Yu, Qingxu; Qin, Wei (International Journal of Agricultural and Biological Engineering, 2020)
Panax notoginseng is grown mainly in Yunnan Province. Under the present high-density planting patterns for the plant, to solve the problems of a high rate of seed damage and the inability to use a traditional single air-blowing metering device, this paper designs a six-row air-blowing centralized precision seed-metering device for P. notoginseng to realize mechanized precision seeding of this species. This paper describes the working principle of the seed-metering device, and the main structural parameters are determined by combining theoretical calculations with simulation analysis. A mechanics model of the seed filling, cleaning and pressing processes of the seed-metering device was constructed. The seeds of P. notoginseng in Yunnan Province were selected as experimental subjects. An experimental study on the seed-metering performance of the seed-metering device was carried out using the quadratic rotation orthogonal combination test method. The outlet pressure of the air nozzle, forward velocity and cone angle of the hole were selected as test factors. Mathematical models of the grain spacing qualified index, miss index, multiple index and the coefficient of variation of the row displacement consistency were established to analyze the order of factors affecting indicators. Through parameter optimization, the optimum combination of parameters was determined as follows: the cone angle of the hole is 50°, the forward velocity is less than 0.73 m/s, and the outlet pressure of the air nozzle is 0.32-0.52 kPa. The qualified index of grain spacing is higher than 94%, the miss index is less than 3%, the multiple index is less than 5%, and the coefficient of variation of the row displacement consistency is less than 5%. The test results are essentially consistent with the optimization results. The metering device meets the requirements of precision seeding of P. notoginseng. This study provides a basis for the design of a six-row air-blowing centralized precision seed-metering device for P. notoginseng. Keywords: Panax notoginseng, air blowing, seed-metering device, optimization design, air distribution mechanism DOI: 10.25165/j.ijabe.20201302.5161 Citation: Lai Q H, Sun K, Yu Q X, Qin W. Design and experiment of a six-row air-blowing centralized precision seed-metering device for Panax notoginseng. Int J Agric & Biol Eng, 2020; 13(2): 111–122.